Study of optimum conditions for Polyhydroxybutyrate production from local isolate of Bacillus cereus - Al-Sahlany , Shayma; Al-Sahlany , Shayma (University of Thi-Qar Journal of Science, 2015)
The highest Polyhydroxybutyrate (PHB) production from Bacillus cereus B5 were 6.2 k/ L, biomass 8.4 g/ L and 73.8 % , the yield by the using optimum conditions , incubation temperature 35 C, for 48 hours aerobically by using shaking incubator on 150 rpm / min , 2% inoculum volume, the pH value was 7, and the production media was content 1% glucose as carbon source and 0.25 % peptone as nitrogen source.